1958
DOI: 10.1136/bmj.2.5107.1264
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function in Scleroderma

Abstract: It has been known for some time that changes caused by scleroderma-progressive systemic sclerosisI0-appear not only on the skin but also in the internal organs, especially the gastro-intestinal tract, lungs, and heart. Only

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1962
1962
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Such a metabolic disorder is not regularly correlated with PAH clearance values, which are usually considered an early index of renal involvement in PSS (22), and might represent the first appearance of abnormal renal function in this disease.…”
Section: Discussionmentioning
confidence: 98%
“…Such a metabolic disorder is not regularly correlated with PAH clearance values, which are usually considered an early index of renal involvement in PSS (22), and might represent the first appearance of abnormal renal function in this disease.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence indicating that the renal circu lation may be affected before renal failure occurs in scleroderma was provided by Urai et al [19]. They showed significant reductions in renal plasma flow but normal glomerular filtration rates in 23 of 25 patients with sclero derma of varying severity.…”
Section: Renal Function Abnormalitiesmentioning
confidence: 94%
“…The work by Vrai et al [19] demonstrating re ductions in renal plasma flow in scleroderma patients with normal glomerular filtration rates led these authors to suggest that there was vasoconstriction of the efferent arterioles. Cannon et al [1] showed reductions in renal cortical blood flow during induction of Ray naud's phenomenon and increments in flow after administration of aminophylline into the renal artery.…”
Section: Pathogenesismentioning
confidence: 99%
“…While renal blood flow has been found to be reduced in PSS patients in the absence o f severe hypertension or renal failure [6], no abnormalities of the renin-angiotensin system or of the sympathetic nervous system have been reported in this situation [9,10], In the present study, the possibility that a defect of a vasodilator system might have a pathogenic role in the renal vascular abnormalities of PSS was examined. The urinary excretion rates of kallikrein and kinin and of immunoreactive prostaglandin E (iPGE) were determined under controlled sodium and potassium intakes in a group of patients that had no clinical evidence of heart failure, severe hypertension or renal failure.…”
Section: Progressive Systemic Sclerosis (Pss) Is a Disease Of Unknownmentioning
confidence: 97%
“…and renal [5,6] circulations. Renal involvement is common in PSS and oliguric acute renal failure is the leading cause of death in this disease [5,7,8], Studies from this labora tory have shown marked depressions of renal cortical blood flow in PSS patients with renal failure [5], Reduced renal blood flow has also been documented in PSS patients in the absence of renal failure and hypertension under basal conditions [6] and during induction of Raynaud's phenomenon [5].…”
Section: Progressive Systemic Sclerosis (Pss) Is a Disease Of Unknownmentioning
confidence: 99%